A comparison of bird communities in natural and revegetated grasslands in south Brazil - Becker, Rafael Gustavo; Paise, Gabriela; Pizo, Marco Aurélio [UNESP] (Springer Nature, 2019)
Natural grasslands are declining due to loss, fragmentation and degradation, resulting in the decline of grasslandassociated bird species. The Pampas Biome in south Brazil is not exception to this worldwide trend, facing the expansion of croplands and afforestation with exotic tree plantations for cellulose production. To cope with the continuous degradation and loss of grasslands, restoration is an important conservation strategy, but basic information regarding the response of the fauna to restoration practices in southeastern South America grasslands is lacking. Here we compared the structure of bird communities in natural grasslands and revegetated grasslands after mining by planting native and exotic grasses. We sampled birds using 5-min point counts with unlimited radius in three replicates of each habitat (natural and revegetated grasslands; average size 22.2 ± 2.3 ha). We also compared the vegetation density between the two habitat types. The structure of bird communities at natural and revegetated grasslands differed, with natural grasslands presenting higher species richness (42 vs. 35 species) and abundance (1459 vs. 839 records) than revegetated areas, and also a distinct species composition. Ten of the 11 grassland species that were associated to one of the two habitat types occurred more frequently in natural grasslands, which had higher vegetation density than revegetated areas. Even a decade after the beginning of the restoration process, revegetated areas did not resemble natural grasslands in bird species richness, abundance, and composition. These results differed from another study conducted in the Brazilian Pampas in which native plant species were used to actively restore a grassland. Therefore, until we have additional studies addressing the use of exotic grasses for the recovery of bird communities in South America grasslands, we encourage greater representation of native plant species in restoration projects.
Keywords: Exotic grasses; Habitat restoration; Mining; Pampas biome